ANALISIS PRAGMATIK DALAM PENGGUNAAN BAHASA IKLAN DI SURAT KABAR THE JAKARTA POST ONLINE - Dias Andris Susanto; Pipit Mugi Rahayu (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2014)
The purpose of this study are to describe and explain: 1) to determine how the use of the types of speech acts in the language of the ads found in the newspaper The Jakarta Post Online, 2) to determine how the process or how the formation of the language of advertising in letter The Jakarta Post online news as linguistic teaching materials. Research Design in this research was descriptive qualitative, which means providing indepth explanation of the phenomenon or object in a systematic way, based on the facts and accuracy (Moleong,2006:5). The authors applied this research method inorder to determine how to use the types of speech acts (speech act) in the language of the ads found in the newspaper The Jakarta Post Online, and how the formation of the language of advertising in the newspaper The Jakarta PostOnline. The Jakarta Post Online as the subject of this study .Object of this research was thatthere were ads on the newspaper The Jakarta Post Online